The Effect of Pictures in Writing Narrative Text of Students of Junior High - Siahaan, Mungkap Mangapul; Sinaga, Asima Rohani; Sirait, Jumaria; Sibarani, Ega Putri Sani; Pasaribu, Sunggul (Future Science / FSH-PH Publications, 2023)
This study aims to investigate whether or not there is an effect of Picture Teaching Model in teaching narrative text for the ninth grades students of SMPN 2 Pematangsiantar. The method used in the research is a true experimental design method. In the method, the researcher used two classes as one control class and one experimental class. The experimental class was taught with a treatment as Picture Teaching Model and the control class was taught with a conventional model. The sampling was selected by random sampling, as class 〖IX〗^5 as control class consisted of 32 students and class 〖IX〗^7 as experimental class consists of 32 students. The means of experimental group was higher that that the control group (20.75 – 14.53 = 2.87), the two means of both experimental and control group was different. If this difference can show that t-test is greater than t-table, that it is significant. The value of t-test has higher than t-table 6.98>2.00. It means that there is a significances after Picture Teaching Model is used to teach writing narrative text. Based on calculation of t-test is (6.98) is higher than t-table at the level of significance (2.00). If the result of t-test is higher than t-table (6.98>2.00), the null hypothesis (H0) is rejected and alternative hypothesis (Ha) is accepted. The results state that there is an influence of Picture Teaching Model in Narrative text learning in class IX of SMPN 2 Pematangsiantar.